2010
DOI: 10.1097/jto.0b013e3181ce3d1d
|View full text |Cite
|
Sign up to set email alerts
|

High MET Gene Copy Number Leads to Shorter Survival in Patients with Non-small Cell Lung Cancer

Abstract: Our results suggest that increased MET GCN would be an independent poor prognostic factor in SCC of the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
143
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(156 citation statements)
references
References 33 publications
9
143
3
1
Order By: Relevance
“…21,46,55,56). Interestingly, a much greater incidence of MET amplification, ranging from 5% to 22%, has been reported in patients with NSCLC following treatment with erlotinib/gefitinib (Table 1; refs.…”
Section: Met Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…21,46,55,56). Interestingly, a much greater incidence of MET amplification, ranging from 5% to 22%, has been reported in patients with NSCLC following treatment with erlotinib/gefitinib (Table 1; refs.…”
Section: Met Amplificationmentioning
confidence: 99%
“…Amplification of MET (and overexpression of the protein) is also a common event in brain metastases of NSCLC (59). Furthermore, fluorescence in situ hybridization (FISH)-positive MET status predicts worse survival in patients with advanced NSCLC (56,60). An analysis of OS based on MET FISH status-derived GCN revealed that increased GCN is an independent negative prognostic factor in surgically resected NSCLC, with OS of 25.8 months for patients with MET !5 copies/cell compared with 47.5 months for patients with MET <5 copies/cell (P ¼ 0.0045; ref.…”
Section: Met Amplificationmentioning
confidence: 99%
“…MET gene copy number was estimated using an LSI MET SpectrumRed/CEP7 SpectrumGreen probe (Abbott Molecular) and interpreted using the above University of Colorado Cancer Center system or Cappuzzo criteria (high MET gene copy number; mean ≥ 5 copies per cell) as described previously. 30 …”
Section: Patients and Samplesmentioning
confidence: 99%
“…The two most commonly used criteria are the University of Colorado Cancer Center Criteria (UICC; ref. 50 ) and the Cappuzzo scoring system ( 51 ). Both of these scoring systems, however, evaluate aneuploidy and real MET amplifi cation at the same time.…”
Section: A General Problem: Defi Nition Of Met Amplifi Cationmentioning
confidence: 99%